3D Volumetric Modeling and Microvascular Reconstruction of Irradiated Lumbosacral Defects after Oncologic Resection - Garcia-Tutor, Emilio; Romeo, Marco; Chae, Michael P.; Hunter-Smith, David J.; Rozen, Warren Matthew (Frontiers in Surgery, 2016)
Background: Locoregional flaps are sufficient in most sacral reconstructions. However, large sacral defects due to malignancy necessitate a different reconstructive approach, with local flaps compromised by radiation and regional flaps inadequate for broad surface areas or substantial volume obliteration. In this report, we present our experience using free muscle transfer for volumetric reconstruction in such cases, and demonstrate 3D haptic models of the sacral defect to aid preoperative planning. Methods: Five consecutive patients with irradiated sacral defects secondary to oncologic resections were included, surface area ranging from 143-600cm2. Latissimus dorsi-based free flap sacral reconstruction was performed in each case, between 2005 and 2011. Where the superior gluteal artery was compromised, the subcostal artery was used as a recipient vessel. Microvascular technique, complications and outcomes are reported. The use of volumetric analysis and 3D printing is also demonstrated, with imaging data converted to 3D images suitable for 3D printing with Osirix software (Pixmeo, Geneva, Switzerland). An office-based, desktop 3D printer was used to print 3D models of sacral defects, used to demonstrate surface area and contour and produce a volumetric print of the dead space needed for flap obliteration. Results: The clinical series of latissimus dorsi free flap reconstructions is presented, with successful transfer in all cases, and adequate soft-tissue cover and volume obliteration achieved. The original use of the subcostal artery as a recipient vessel was successfully achieved. All wounds healed uneventfully. 3D printing is also demonstrated as a useful tool for 3D evaluation of volume and dead-space. Conclusion: Free flaps offer unique benefits in sacral reconstruction where local tissue is compromised by irradiation and tumor recurrence, and dead-space requires accurate volumetric reconstruction. We describe for the first time the use of the subcostal artery as a recipient in free flap sacral reconstruction. 3D printing of haptic bio-models is a rapidly evolving field with a substantial role in preoperative planning.